A pig model exploring the postnatal hair follicle cycle - Li, Shujuan; Zou, Quan; Jiang, Yao; Wang, Yi; Ding, Xiangdong (Frontiers in Cell and Developmental Biology, 2024)
The hair follicle (HF) is a micro-organ capable of regeneration. A HF cycle consists of an anagen, catagen and telogen. Abnormalities in the HF cycle can lead to many hair disorders such as hair loss. The pig is a good biomedical model, but there are few data on their HF cycle. The aim of this study was to classify the pig HF cycle and determine the feasibility of the pig as an animal model for human HF cycle. We used skin samples from 10 different postnatal (P) days Yorkshire pigs to determine the key time points of the first HF cycle in pig. By morphological observation and detection of markers at different stages, pig HF cycle was classified into three main periods -the first anagen until P45, catagen (P45-P85), telogen (P85-P100), and next anagen (>P100). In addition, we examined the expression of important genes AE15, CD34, Versican, Ki67 et al. related to the HF cycle at different stages of pig HF, indicating that pig and human share similarities in morphology and marker gene expression patterns of HF cycle. Our findings will facilitate the study of HF cycle and offer researchers a suitable model for human hair research.